2020
DOI: 10.1039/d0ra00188k
|View full text |Cite
|
Sign up to set email alerts
|

Large magnetodielectric effect and negative magnetoresistance in NiO nanoparticles at room temperature

Abstract: This work presents NiO nanoparticles synthesized by simple chemical route showing large magnetodielectric effect at room temperature resulted from Maxwell–Wagner polarization effect which was arising due to large negative magnetoresistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 83 publications
2
8
0
Order By: Relevance
“…The lattice parameter value was verified via an HR-TEM image (Figure c). The d-spacing value of the (111) plane calculated using the XRD results is about 0.241 nm, which shows consistency with the TEM analysis result (0.241 nm in TEM). In the fast Fourier transformation (FFT) image (Figure d), the distances between the symmetrically positioned spots were measured via the GMS 3 program.…”
Section: Results and Discussionsupporting
confidence: 81%
“…The lattice parameter value was verified via an HR-TEM image (Figure c). The d-spacing value of the (111) plane calculated using the XRD results is about 0.241 nm, which shows consistency with the TEM analysis result (0.241 nm in TEM). In the fast Fourier transformation (FFT) image (Figure d), the distances between the symmetrically positioned spots were measured via the GMS 3 program.…”
Section: Results and Discussionsupporting
confidence: 81%
“…5(a), (c) and (e) , Co 2p spectra were fitted and thereby deconvolution resulted in two peaks at 780.3 eV and 781.9 eV associated with the two oxidation states of Co 2+ and Co 3+ respectively. 26 Similarly, two deconvoluted Ni 2p spectra with peak centred at 854.6 eV and 855.8 eV were assigned to Ni 2+ and Ni 3+ respectively 33 as revealed in Fig. 5(b), (d) and (f) .…”
Section: Resultsmentioning
confidence: 84%
“…32 Several research ndings revealed that MR can have negative values as well. 26,33 In disordered systems, spin-orbit interaction plays inuential role in governing the sign of MR. [34][35][36] Interplay between magnetism and electrical properties was explored in BaTiO 3 -SrFe 12 O 19 nanocomposites. 37 Positive and negative MD effect depending on frequency and temperature was observed in these nanocomposites which may be attributed to the induced internal magnetic eld and space charge/interfacial polarization respectively.…”
Section: Introductionmentioning
confidence: 99%
“…At very low H ext , the neighboring GBs can align themselves in order to enhance the extent of electron tunnelling across the GBJ and thus lowering the electrical resistivity. 22,42 The validity of this model for our catalyst is shown by the fitting of magnetoresistance data with an exponential decay function, R H = R 0 + R 1 exp(−H/H s ), 22,42,43 where R 0 denotes the scattering-independent electrical resistivity of the medium and R 1 denotes the electrical resistivity arising from spin-dependent scattering. As extracted from the fitting, H s of 0.2205 T agrees well with the electrochemical magnetochronoamperometry, where the volume increment in H 2 evolution saturates at ∼0.2 T (Figure 1g).…”
Section: ■ Results and Discussionmentioning
confidence: 87%